Is the Place of Women in Neo-Sarmatian Social Hierarchy Always Below Men? On the Example of Borderland She-Wolves in the Prose of Jacek Komuda, Andrzej Pilipiuk and Others - Tauer, Sebastian (Literatura Ludowa. Journal of Folklore and Popular Culture, 2026)
The article analyzes the characters of Borderland she-wolves in the context of Neo-Sarmatian literature in the novels by such authors as Jacek Komuda or Andrzej Pilipiuk. Borderland she-wolves, inspired by the image of strong independent women living in the border lands of the Eastern part of the Commonwealth constitute an interesting element of literary Neo-Sarmatism. The study analyzes how these characters are inscribed into the hierarchy that reflects the vision of social structure created by the radical right wing Neo-Sarmatians. Due to the ability for self-determination, which carries out the libertarian principle of self-ownership and a particular sense of honor, expressed in the obligation to fight in an open manner, worthy of a well-born person, Borderland she wolves can take a place at the top of the social ladder, together with the Cossacks or the noblemen. This also demonstrates that it is impossible to talk about women in Neo-Sarmatian writing as about a homogeneous group. Similarly to men, they are divided into sub-groups which – depending on the features displayed by their representatives – can take up higher or lower positions in social hierarchy determined by honor and the principle of self-ownership.